Controls on the expression of igneous intrusions in seismicreflection data - Magee,C; Maharaj,SM; Wrona,T; Jackson,CA-L (Geosphere, 2015)
The architecture of subsurface magma plumbing systems influences a variety of igneous processes, including the physiochemical evolution of magma and extrusion sites. Seismic reflection data provides a unique opportunity to image and analyze these subvolcanic systems in three dimensions and has arguably revolutionized our understanding of magma emplacement. In particular, the observation of (1) interconnected sills, (2) transgressive sill limbs, and (3) magma flow indicators in seismic data suggest that sill complexes can facilitate significant lateral (tens to hundreds of kilometers) and vertical (<5 km) magma transport. However, it is often difficult to determine the validityof seismic interpretations of igneous features because they are rarelydrilled, and our ability to compare seismically imaged features to potential field analogues is hampered by the limited resolution of seismic data. Here we use field observations to constrain a series of novel seismic forward models that examine how different sill morphologies may be expressed in seismic data. By varying the geologic architecture (e.g., host-rock lithology and intrusion thickness) and seismic properties (e.g., frequency), the models demonstratethat seismic amplitude variations and reflection configurations can beused to constrain intrusion geometry. However, our results also highlight that stratigraphic reflections can interfere with reflections generated at the intrusive contacts, and may thus produce seismic artifacts that could be misinterpreted as real features. This study emphasizes the value of seismic data to understanding magmatic systems and demonstrates the role that synthetic seismic forward modeling can play in bridging the gap between seismic data and field observations.